Male genital tract immune response against Chlamydia trachomatis infection. Issue 4 (October 2017) - Mackern-Oberti, Juan Pablo; Motrich, Rubén Darío; Damiani, Maria Teresa; Saka, Héctor Alex; Quintero, Cristian Andrés; Sánchez, Leonardo Rodolfo; Moreno-Sosa, Tamara; Olivera, Carolina; Cuffini, Cecilia; Rivero, Virginia Elena
Abstract : Chlamydia trachomatis is the most commonly reported agent of sexually transmitted bacterial infections worldwide. This pathogen frequently leads to persistent, long-term, subclinical infections, which in turn may cause severe pathology in susceptible hosts. This is in part due to the strategies that Chlamydia trachomatis uses to survive within epithelial cells and to evade the host immune response, such as subverting intracellular trafficking, interfering signaling pathways and preventing apoptosis. Innate immune receptors such as toll-like receptors expressed on epithelial and immune cells in the genital tract mediate the recognition of chlamydial molecular patterns. After bacterial recognition, a subset of pro-inflammatory cytokines and chemokines are continuously released by epithelial cells. The innate immune response is followed by the initiation of the adaptive response against Chlamydia trachomatis, which in turn may result in T helper 1-mediated protection or in T helper 2-mediated immunopathology. Understanding the molecular mechanisms developed by Chlamydia trachomatis to avoid killing and host immune response would be crucial for designing new therapeutic approaches and developing protective vaccines. In this review, we focus on chlamydial survival strategies and the elicited immune responses in male genital tract infections.